Validation of the Arabic version of the Diabetes Therapy-Related Quality of Life Questionnaire (DTR-QOL) in Tabuk, Saudi Arabia: a pilot study - Alshadfan, Hisham; Mirghani, Hyder; Alrasheed, Tariq; Ibrahim, Yassin; Aljohani, Samar; Alanzi, Tahani; Alshehri, Sami; Nurdin, Armania; Abdullah, Muhammad Nazrul Hakim (Journal of Medical Science, 2024)
Background: Diabetes mellitus is a chronic disease that significantly influences the patient's quality of life. This serious disease is approaching an epidemic, and the Arab countries are in the diabetes super region. Improving the patient's quality of life is vital for good glycemic control. However, the Diabetes Therapy-Related Quality of Life Questionnaire (DTR-QOL) is not available in Arabic. Thus, we aimed to validate the questionnaire among patients with diabetes in Saudi Arabia. Subjects and methods: This pilot study was conducted among randomly selected 30 patients with diabetes who came for regular follow-up in the Diabetes Center in King Fahd Specialist Hospital in Tabuk City, Saudi Arabia, during March and April 2023. A structured questionnaire based on sociodemographic data and the DTR-QOL was used. The information collected were age, gender, diabetes medications, glycemic indices, lipid profile, fasting insulin, homeostatic model assessment for insulin resistance, and body mass index. Forward/backward translation, expert assessment, and Cronbach's alpha were used to assess the validity and reliability. Results: Out of the 30 patients with diabetes piloted for the questionnaire validation, 60% were females, the mean age was 51.1 ± 14.056 years, and 94% had type 2 diabetes. The internal consistency varied from 0.80 for hypoglycemia to 0.94 for anxiety and dissatisfaction with treatment. The Arabic version of the DTR-QOL is valid and reliable for use among patients with diabetes, with a content validity of 0.938 and Cronbach's alpha of 0.93. Conclusion: The Arabic version of the DTR-QOL is valid and reliable for use among patients with diabetes in Arab countries and has good sensitivity and consistency.